Comparison between a facemask and mouthpiece on breathing mechanics and gas exchange variables during high-intensity exercise - Freemas, J. A.; Wilhite, D. P.; Greenshields, J. T.; Adamic, E. M.; Mickleborough, T. D. (European Journal of Sport Science, 2020)
Gas-collection masks are used as a comfortable alternative to the traditional mouthpiece and noseclip during exercise testing protocols in human performance laboratories. However, these masks may introduce potential problems which could affect metabolic and ventilatory parameters, including gas leaks and added dead space. Therefore, the purpose of this study was to compare breathing mechanics, gas exchange variables and ratings of perceived breathlessness (RPB) during high-intensity exercise between a mouthpiece and face mask. Fourteen men [VO2peak = 55.3 ± 7.3 ml·kg-1·min-1] were recruited to perform 6 min of cycle ergometry (Velotron Pro, RacerMate, Inc., Seattle, WA) at a work rate corresponding to 90% of ?O2peak while breathing on either (1) a mouthpiece (Hans Rudolph, KC, KS) with nose clip, or (2) a face mask (7450, Hans Rudolph, KC, KS). The difference in ?E between the mouthpiece (156.8 ± 23.3 L/min) and face mask (153.3 ± 21.8 L/min) was not significant (p = 0.534). Similarly, there were no significant differences in breathing mechanics, gas exchange variables or RPB. These data suggest that the facemask can continue to be used interchangeably with the mouthpiece and may even be a more comfortable alternative during high-intensity exercise.